(untitled) (Revista Nacional de Odontología, 2020)
Retrograde peri-implantitis is a novel entity that requires the clinician to know the clinical and radiographic characteristics that allow its diagnosis and management, it is considered an infectious and inflammatory pathology characterized by the presence of a clinically symptomatic apical lesion, diagnosed by radiolucency that develops shortly after implant insertion. The objective of this article is to know the entity’s diagnostic and therapeutic criteria, exploring its conservative management through a clinical case The authors present the case of a patient with a history of asymptomatic apical periodontitis associated with the right maxillary central incisor, which was extracted and after bone regeneration of the area and placement of a dental implant, she presented a fistulous tract and an apical lesion associated with a dental implant. After a conservative management with two different antibiotic regimens, the infectious and inflammatory condition was eliminated, therapeutic option that allows to resolve the entity without the need for surgical intervention.